Efforts To Sustain Fresh Water Production in Order to Improve The Performance of Fresh Water Generator On The Mt. Rubra - MP, Alfyansyah; Ridwan, Mohamad; Y Siahaan, Rosna (International Journal of Advanced Multidisciplinary, 2023)
Fresh water generator is an auxiliary aircraft aboard a ship that produces fresh water by evaporating seawater in the evaporator and the seawater is cooled by condensation in a distillation vessel or condenser (condenser), thus producing condensed water called condensate. Fresh water generator running optimally is one of the important factors to support ship operations, especially the results of the fresh water generator used for cooling systems and daily needs on board. This study aims to find out the causes of the problems and efforts that occur in the fresh water generator so that it can maintain fresh water production results in the fresh water generator. While data analysis is to identify the data set that has been obtained, so that the data can be analyzed and the purpose is analyzed in order to get a clearer picture in the preparation of this research both from the problems and the final results. It is hoped that this research research can produce ideas, solutions and appropriate problem solving, both in observing and dealing with the problems raised in this study. Based on research on fresh water production on fresh water generators in MT. Rubra has decreased from 19 tonnes/day to 12 tonnes/day. This is caused by the occurrence of salt deposits on the evaporator plate so that evaporation becomes late and the low pressure of sea water leading to the fresh water generator causes fresh water production to decrease